(untitled) (Conference Zone, 2022)
Newspaper styleis a system of interrelated lexical, phraseological and grammatical means which is perceived by the community speaking the language as a separate unity that basically serves the purpose of informing and instructing the reader. To attract the reader’s attention specific headlines, space ordering, a large proportion of dates, personal names of countries, institutions, and individuals are used. Since the primary function of newspaper style is to impart information, only printed matter serving this purpose comes under newspaper style proper.The extremely common blending of textural modes by means of linear and layered blending is brought out, particularly through a ‘case study’of one of the editorials This article discusses about the blending and conversion in newspaper style.